A realist social ontology of religion. Issue 2 (3rd April 2017) - Schilbrack, Kevin
ABSTRACT: Jonathan Z. Smith famously pointed out that the concept of 'religion' is not universal but emerged only in the modern West. Several scholars have drawn from Smith the non-realist implication that the existence of religion apart from that concept is an illusion. The word 'religion, ' they say, does not refer to something out there in the world. In this article, the author argues that Smith's point is open to a realist interpretation according to which religion exists in the world, as a transhistorical and transcultural reality, even apart from the concept. To make this case, the author outlines and responds to non-realist positions that draw on genealogical, deconstructive, and linguistic arguments, as well as to the alternative proposal that 'religion' is simply a heuristic device. In short, the goal of this article is to argue that a realist social ontology provides the better understanding of the central theoretical term in our field.